Effect of nanoencapsulated crude palm oil addition on the oxidative stability of salad dressing in an accelerated oxidation test (Research, Society and Development, 2020)
The effect of the addition of nanoencapsulated crude palm oil (NE-CPO) as antioxidant in a salad dressing using accelerated oxidation (Schaal Oven Test) was evaluated. The encapsulation efficiency (EE), particle size (PS), Zeta potential (Zp) and polydispersity index (PDI) was determined. Crude palm oil (CPO) and NE-CPO were evaluated for total carotenoids (TC) and antioxidant activity (AA) using the ABTS method. Analysis of the centesimal composition and TC in three developed mustard salad dressings (A control/B -control + NE-CPO/C -control + BHA and BHT) were carried out. OPB-L, OBP-NE e os molhos foram submetidos ao Schaal Oven Test em estufa (60 ± 5º C/15 dias/circulação de ar).  OPB-L, OBP-NE and sauces were evaluated by Schaal Oven Test in an oven (60 ± 5º C/15 days/air circulation). After 15 days, the acidity value (AV), peroxides value (PV) and conjugated dienes (CD) and trienes (CT) were determined. NE-CPO presented EE of 95.66%, PS of 0.29 µm, particle size heterogeneity (PDI 1.00), Zp of -41.80 mV, indicating good stability of the particles, and 12.11% of AA. The NE-CPO and the dressing B presented 561.77 ± 10.97 µg.g-1 and 442.31 ± 12.14 µg.g-1 of TC, respectively. The dressings had no difference in the centesimal composition. NE-CPO showed greater increase in acidity than CPO, PI and lower CD, and similar CT after 15 days. The dressing C presented a greater stability when compared to dressings A and B, followed by dressing B, which was more stable than dressing A. It was concluded that NE-CPO can be an alternative to the synthetic antioxidants BHA and BHT in salad dressings.